Analisis Penerapan Sistem Manajemen ISO 9001:2015 di Sekolah Dasar : Narrative Literature Review. - Azahra, Arinka Dwi; Putri, Dwiayu Nabila (AGUSPATI RESEARCH INSTITUTA, 2024)
Abstract - The purpose of writing this article is to describe the application of the ISO 9001:2015 quality management system to 3 (three) articles. This data collection technique by way of documentation, interviews, and observation. It is used to get the required information. In this modern era, all forms of service activities related to ensuring customer satisfaction are a must for an educational institution, both government and private. Likewise in academic services in schools, where implementation must guarantee the process of teaching and learning activities that aim to increase customer satisfaction. To support the implementation of ISO 9001:2015 to improve the quality of academic services in elementary schools requires a very high commitment from all school members, superior quality human resources, completeness of adequate infrastructure and an environment that provides comfort and calm in learning activities, so that the implementation of ISO to run smoothly. The research results show that the ISO 9001:2015 quality management system is going well. This is proven by the existence of school efforts that always maintain customer trust, curriculum that is in accordance with improving the quality of education, running programs and targets that have been set, always involving school members, ongoing evaluation, solving problems using existing data and facts and the existence of cooperation what schools do with outsiders.